Work-Life Balance of Employees Working in Birendranagar Municipality, Surkhet (Journal of Nepalese Management and Research, 2024)
This study examines the impact of working hours, workplace culture, leader and coworker support, and remuneration and rewards on the work-life balance of employees in Birendranagar Municipality, Surkhet. Using an explanatory research design and quantitative approach, data was gathered via a survey questionnaire with a five-point Likert scale. The study included a purposive sample of 180 employees. Results indicate that while working hours and workplace culture did not significantly influence work-life balance, leader and coworker support (LCS) and remuneration and rewards (RNR) emerged as critical determinants. LCS showed a strong positive correlation with work-life balance, underscoring the importance of supportive leadership. Similarly, fair remuneration and rewards positively impacted work-life balance, emphasizing the significance of equitable compensation practices. Recommendations include enhancing leader and coworker support systems and improving remuneration and reward structures to promote employee well-being and organizational effectiveness. Fostering a positive workplace culture that supports flexibility and mutual respect is also advised to enhance the overall work-life balance among employees.